2022
DOI: 10.14309/ajg.0000000000001804
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Health in Sexual and Gender Minority Populations

Abstract: It has been over 50 years since the Stonewall Inn Riots in June 1969, a seminal event for the lesbian, gay, bisexual, transgender, queer, intersex, and other sexual and gender-diverse minorities (LGBTQI1, or lesbian, gay, bisexual, transgender, queer, intersex, and everyone else) rights movement. However, sexual and gender minority (SGM) individuals still face discrimination and harassment due to their sexual orientation or gender identity. As such, the National Institute on Minority Health and Health Disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…have an increased risk for health problems. [4][5][6] In recent years, the number of children in families with parents who are lesbian, gay, bisexual, transgender and queer has increased. [7][8][9] A report in 2018 showed that, in the USA, same-sex couples are seven times more likely than different-sex couples to be raising an adopted or foster child, and there are an estimated 114 000 same-sex couples raising children.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…have an increased risk for health problems. [4][5][6] In recent years, the number of children in families with parents who are lesbian, gay, bisexual, transgender and queer has increased. [7][8][9] A report in 2018 showed that, in the USA, same-sex couples are seven times more likely than different-sex couples to be raising an adopted or foster child, and there are an estimated 114 000 same-sex couples raising children.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Sexual and gender minorities is an umbrella term including lesbian, gay, bisexual, transgender, queer, intersex, gender non-conforming people and other populations whose sexual orientation or gender identity and reproductive development is considered outside cultural, societal or physiological norms 1–3. Compared with the heterosexual population, sexual and gender minorities have an increased risk for health problems 4–6. In recent years, the number of children in families with parents who are lesbian, gay, bisexual, transgender and queer has increased 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] To care for this population, clinicians should be aware of liver disease burdens in SGM individuals and risk factors. A recently proposed conceptual framework, adapted from the Minority Stress Model, links the effects of life stressors, psychosocial factors, behavioral factors, and physiologic factors with the burden of gastrointestinal diseases and outcomes for SGM individuals (Figure 1), [3] which we use to frame our presentation of risk factors. For instance, behavioral factors, such as injection drug use (IDU), [12] more common in certain SGM communities, [12] are influenced by minority identity and life stressors (discrimination, violence, stigma, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Yet, SGM-focused research is hampered by inappropriate study design and inaccurate use of sex (biological attributes) vs gender (socially constructed norms varying over time). Recent work has highlighted significant knowledge gaps in SGM-focused digestive health (3). Addressing these deficits must be performed conscientiously through partnership with methodologic experts and community members to ensure high-quality data and ethical engagement with historically marginalized communities.…”
mentioning
confidence: 99%